ASSESSMENT OF LOADING OF ASCORBYL-2-PHOSPHATE AND 6-O-PALMITOYLASCORBIC ACID IN CETYL DIMETHICONE COPOLYOL BASED W/O/W EMULSIONS - Khan, Hira; Ali, Atif (LIFE: International Journal of Health and Life-Sciences, 2018)
W/O/W emulsions with multifaceted nature ensure the ability to incorporate lipophilic as well as hydrophilic compounds based on their solubility. Loading of these compounds in different phases of W/O/W emulsion may affect their constancy. This study was aimed to evaluate the constancy of Ascorbyl-2-phosphate and 6-O-Palmitoylascorbic acid in W/O/W emulsions (F1 and F2). F1 and F2 samples containing Ascorbyl-2-phosphate and 6-O-Palmitoylascorbic acid in different phases of cetyl dimethicone copolyol based W/OW emulsions were analyzed for globule size, rheological behavior and HPLC, immediately after preparation and then at different storage conditions (8°C, 25°C, 40°C and 40°C+75%RH) for 90 days. Rheological analysis showed that at accelerated storage conditions F1 and F2 had shear thinning behaviour of varying shear stress with no influence of location of functional ingredients in the carrier system. Microscopic analysis showed increase in globule size with time, especially at higher temperatures while decreased at low temperatures. HPLC analysis at the end of 90 days showed that 6-O-Palmitoylascorbic acid and Ascorbyl-2-phosphate were almost stable in F1 and F2 W/OW emulsions with no influence of their location in a carrier system. F1 and F2 W/OW emulsions were found stable carriers for Ascorbyl-2-phosphate and 6-O-Palmitoylascorbic acid. This study may contribute to the improvement of formulations with Ascorbyl-2-phosphate and 6-O-Palmitoylascorbic acid to enhance their cosmetic benefits and also provides the direction to evaluate the stability with different concentrations of these compounds.